Analisis Komposisi Jenis dan Kelimpahan Zooplankton di Perairan Kampung Nafri, Kota Jayapura - Sremsrem, Nikodemus; Kubelaborbir, Triana Mansye; Lewaherilla, Niki Elistus (Politeknik Negeri Sambas, 2023)
This study aimed to determine the type, composition, and abundance of zooplankton in the waters of Kampung Nafri. Zooplankton were identified using zooplankton sample identification guidelines, and zooplankton abundance analysis was performed using the Sedgewick Rafter. Purposive sampling was used in this study. Zooplankton sampling was carried out horizontally on the surface of the water using a plankton net which was carried out in the morning around 08:00 - 10:30 WIT at 3 stations. Sampling at each station was done 2 times repetition and the water parameters were done 3 times repetition. In situ measurement of water quality parameters, such as salinity, pH, current speed, and temperature Based on the identification results, there are 11 types of zooplankton that inhabit the waters of Kampung Nafri. The highest value of zooplankton species composition in Nafri Waters was Naplius sp., which was 63%, and the lowest was Temora sp. and Corycaeus sp. by 1%. The highest abundance of zooplankton species in Nafri Waters was Nauplius sp. (Copepoda larvae), with a total abundance of 9,900 ind/l, and the lowest was Corycaeus sp. and Temora sp., with a total abundance of 200 ind/l.